COPOLYMERIZATION OF VINYL CHLORIDE WITH - Matyakubova D.Sh; Matyakubova N.Sh; Xidirova M.N (Journal of Science in Medicine and Life, 2023)
In this study, given that quality is the first priority in the development of polyvinyl chloride (PVC) products, which are increasingly displacing metal products from the consumer market, extending the useful life of polymer products can solve many of the consumer's economic problems.